Level of ochratoxin A in coffee beans (Coffea arabicaL.) from Jaén and San Ignacio, Cajamarca - Tirado, James (2022)
In recent years, the world market has become more demanding in terms of safety, since concentrations that exceed the maximum permissible limits (MPL) cause the rejection of coffee for export. The objective of this research was to quantify the concentration of ochratoxin A (OTA) at different stages of post-harvest processing of coffee. Samples of parchment coffee beans were collected from warehouses of the companies Organización Agraria Cafetalera El Diamante, Jaén; Cooperativa Agraria Cafetalera CASIL LTD, San Ignacio and Cooperativa Agraria y de Servicios Unión de Cafetaleros Ecológicos-UNICAFEC, San Ignacio, in the Cajamarca region of Peru. OTA was quantified by ELISA (enzyme-linked immunosorbent assay) in husk, green gold coffee beans, roasted coffee beans, ground roasted coffee and coffee essence. ANOVA (p=0.05) showed significant differences in the different stages of coffee processing while Tukey (p=0.05) indicated that the highest OTA concentration occurred in green gold coffee - with and without defects. The hypothesis test (p=0.05) showed that, at all stages, the OTA concentration did not exceed the PML (5 μg/kg).